Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1103/physrevb.91.214104
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy tetrahedral polymorphs of carbon, silicon, and germanium

Abstract: Searches for low-energy tetrahedral polymorphs of carbon and silicon have been performed using density functional theory computations and the ab initio random structure searching (AIRSS) approach. Several of the hypothetical phases obtained in our searches have enthalpies that are lower or comparable to those of other polymorphs of group 14 elements that have either been experimentally synthesized or recently proposed as the structure of unknown phases obtained in experiments, and should thus be considered as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 90 publications
10
64
0
Order By: Relevance
“…3b) is nearly the same as for the phonons in diamond cubic Si, measured by inelastic neutron scattering. At ambient temperature, the pressure shift of the A (6) g mode of Si 24 is approximately the same as the pressure shift of the single Raman mode of diamond cubic Si 12 , although these authors also report some negative Grüneisen parameters for two-phonon Raman features.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…3b) is nearly the same as for the phonons in diamond cubic Si, measured by inelastic neutron scattering. At ambient temperature, the pressure shift of the A (6) g mode of Si 24 is approximately the same as the pressure shift of the single Raman mode of diamond cubic Si 12 , although these authors also report some negative Grüneisen parameters for two-phonon Raman features.…”
Section: Discussionmentioning
confidence: 90%
“…The vertex interactions that give the strengths of phonon-phonon interactions may also change with ∆P . 3g vibrational mode involves more bending of interatomic bonds, whereas bond stretching dominates most other modes such as A (6) g . It is typical for bond stretching in solid crystals to be associated with positive Grüneisen parameters and positive thermal expansion 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Recent ab initio random structure searches identified solids with P4 2 =ncm 14 and P4 1 2 1 2 (Ref. 15) symmetries as possible candidates for the elusive Si-XIII phase, and a new low energy structure (Pbam) with an estimated direct gap of 1.4 eV. 15 Another recent study identified a dynamically and thermally stable hexagonal phase, named h-Si 6 , with a direct band gap of 0.61 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon crystals share many structural similarities with silicon and germanium because of their common s 2 p 2 valence electron configuration 23,24 , thus it is instructive to compare the structural form and relation among various polymorphs of these elements. Silicon and germanium crystallize in cubic diamond structure at ambient conditions; they transform to the β-Sn phase at high pressure and turn into the BC8 and R8 Si and ST12 Ge phase upon decompression [25][26][27] .…”
mentioning
confidence: 99%